How costly is the Sarbanes Oxley Act? Evidence on the effects of the Act on corporate profitability - Ahmed, Anwer S.; McAnally, Mary Lea; Rasmussen, Stephanie; Weaver, Connie D. (Journal of Corporate Finance, 2010)
The Sarbanes-Oxley Act (SOX) was intended to protect investors by improving the accuracy and reliability of corporate disclosures. However, critics have argued that the costs of SOX far outweigh its intended benefits. Prior studies based on stock-price reactions to SOX-related events document mixed evidence on the expected impact of SOX. In contrast, we provide evidence on the net realized costs of SOX by examining its impact on operating profitability. We find that average cash flows decline by 1.3% of total assets after SOX. These costs are more significant for smaller firms, for more complex firms, and for firms with lower-growth opportunities. Annually, these costs range from $6million for smaller firms to $39million for larger firms. Further, we document that net SOX-related costs are not limited to one-time expenses associated with internal-control design and implementation. In aggregate, for the 1428 firms in our sample, these costs amount to about $19billion per year. Profitability is lower for up to four years post-SOX. To our knowledge, ours are the first estimates of the realized net costs imposed by SOX.